PERLINDUNGAN HUKUM PENGGUNA JASA TUKANG GIGI TERHADAP DUGAAN MALPRAKTIK - Rizafaza, Dicky Nur Oktaviano; Mangesti, Yovita Arie (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This legal research aims to determine the regulation of the practice of dental artisans in health services as well as to determine the legal protection of dental artisan service users in the practice of dental artisans. This research was conducted using normative legal research methods. The research approach is a legal approach (statute approach) and a conceptual approach (conceptual approach). Based on this research, it was found that the regulation regarding dental practice refers to the Regulation of the Minister of Health no. 39 of 2014 concerning the Guidance, Supervision, Licensing and Employment of Dentists issued based on the Constitutional Court Decision Number 40/PUU-X/2012 which is a Judicial Review decision. This rule does not provide legal protection for dental artisans who experience malpractice. Violations committed by dental artisans in carrying out their work cause victims to suffer losses. The legal implication of the absence of complete positive legal regulations and legal certainty from the government is an opportunity for dental artisans to practice or act beyond their authority, which results in the emergence of allegations of malpractice, which incur losses for consumers who perform dental care for the dental artisan. Legal protection should be provided through a new law on the practice of dental artisans which contains the authority of dental artisans so that there is a limit to the authority of dental artisans who are different from dentists. For dental artisans who practice as if they were dentists, they have violated Article 78 Number 29 of 2004 concerning Medical Practices with criminal sanctions.